Nonverbal Communication in Rituals on Irish Pilgrimage Routes - Bożena Gierek (Religions, 2022)
There are endless lists of academic publications on pilgrimage and on nonverbal communication, but very rarely if at all, do these two phenomena meet together in the same one, hence the author’s attempt to bring them together here. In this article the author discusses nonverbal communication in the context of pilgrimage rituals. Since rituals are carried out both physically and mentally, their performance requires the involvement of all the senses. A ritual may be verbal or nonverbal and very often is both. All elements of the ritual send a message. Thus, ritual communicates—it is a source of information about the individual retrieved by others—but it is not only that, as it also effects the mind, thoughts and spirituality of the individual. It has enormous influence on the well-being of a person; it is therapeutic. The author describes and analyzes single rituals related to the well, the tree, various kinds of stones, and other objects located on pilgrimage routes. While doing this, the author takes a phenomenological approach. She bases her analysis of nonverbal communication mainly on ethnographic materials. She also utilizes sources from the areas of archeology, anthropology, sociology and psychology. They are supplemented by her own participant observation at many pilgrimage places in Ireland over the period 1995–2012.